2006
DOI: 10.2495/wp060161
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of water withdrawal effect on water quality of the downstream river at the Mamloo Dam site using the QUAL2E model

Abstract: Mamloo Dam is under construction downstream of the Jajrood River to supply Varamin plain's irrigation water, flood control and produce energy.The river water quality as DO, BOD and temperature and its self-purification capacity was studied to define the minimum safe water flow downstream of the dam.The results show that the water quality will not change considerable upstream of the Parchin complex. However, after the complex outfall, the river water quality changes severely; even the effluent is treated up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Moreover, in the study by Dadollahi et al bad water quality of the Karoon River was due to entering sewage plant saponification (14). In Torabian et al study, decline of water quality was due to building wastewater around the area in 2008-2009 (18). The classification of river water (Tajen River) by using the WQI showed that upstream stations had pure, clean, and healthy water and downstream stations had bad quality, which is similar to the result of this research (17).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, in the study by Dadollahi et al bad water quality of the Karoon River was due to entering sewage plant saponification (14). In Torabian et al study, decline of water quality was due to building wastewater around the area in 2008-2009 (18). The classification of river water (Tajen River) by using the WQI showed that upstream stations had pure, clean, and healthy water and downstream stations had bad quality, which is similar to the result of this research (17).…”
Section: Discussionsupporting
confidence: 82%
“…This classification was presented in 1948 by Wilcox and three years later was completed by Toren. Today, this index is considered a common method of water classification for agricultural purposes (7,18). The two factors of electrical conductivity (EC) and sodium adsorption ratio (SAR) are considered and each of them is converted into four parts that totally create 16 groups.…”
Section: Introductionmentioning
confidence: 99%